2013
DOI: 10.1063/1.4792201
|View full text |Cite
|
Sign up to set email alerts
|

Single polymer chains in poor solvent: Using the bond fluctuation method with explicit solvent

Abstract: We use the bond fluctuation model with explicit solvent to study single polymer chains under poor solvent conditions. Static and dynamic properties of the bond fluctuation model with explicit solvent are compared with the implicit solvent model, and the Θ-temperatures are determined for both solvent models. We show that even in the very poor solvent regime, dynamics is not frozen for the explicit solvent model. We investigate some aspects of the structure of a single collapsed globule and show that rather larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…In Figure we show the frequency of polymer translocation, T R ≡ 1/τ, on the basis of the inverse mean first escape time. There, we also include simulation results on the number of polymer translocations detected during MC simulations. , Excellent agreement is found for all chain lengths using the diffusion constant D ∝ 1/ N of the chain and rescaling the time by a factor of order unity. The results demonstrate further that introduction of Γ ∝ N –1/3 is sufficient to reproduce the chain-length dependence as determined by the globular conformations.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…In Figure we show the frequency of polymer translocation, T R ≡ 1/τ, on the basis of the inverse mean first escape time. There, we also include simulation results on the number of polymer translocations detected during MC simulations. , Excellent agreement is found for all chain lengths using the diffusion constant D ∝ 1/ N of the chain and rescaling the time by a factor of order unity. The results demonstrate further that introduction of Γ ∝ N –1/3 is sufficient to reproduce the chain-length dependence as determined by the globular conformations.…”
mentioning
confidence: 76%
“…Inspection of radial globule density distributions reveals that the total diameter of the diffuse surface layer can be of the order of the membrane thickness. 20,21 Length scales are not sufficiently separated to treat the polymer either as an inert sphere or as a random coil only. We note further that the interface of the globule exposes sections of fluctuating strands that obey nearly Gaussian statistics.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…28 We believe that the usage of explicit solvent and hydrodynamic interactions is very important and a key to find crumpled globule after the collapse. Sommer et al recently presented the results of the coil-to-globule transition with explicit solvent particles 31 and have shown that only explicit solvent allows to simulate polymer behavior in a very poor solvent.…”
Section: Introductionmentioning
confidence: 99%